Sertifikasi Tanah Pusako Tinggi ditinjau dari Maqashid Syariah - Yulia Putri; Zul Efendi (Program Studi Magister Hukum Islam - UIN Bukittinggi, 2025)
This study examines the certification of Pusako Tinggi land within the Minangkabau community from the perspective of Maqashid Syari'ah. Pusako Tinggi land, which is inherited through a matrilineal lineage, holds significant economic and social value and is governed by Minangkabau customary law. However, there has been a growing need for land certification to provide legal certainty in a modern context. This certification process raises various questions, particularly concerning its alignment with the principles of Maqashid Syari'ah, which emphasize the protection of religion, life, intellect, lineage, and property. This research aims to analyze the extent to which the certification process of Pusako Tinggi land aligns with the principles of Maqashid Syari'ah and its impact on the sustainability of customary values and the welfare of the community. The study employs a qualitative approach using library research methods. The analysis shows that land certification can provide legal certainty and protection of property (hifz al-mal), but it must be carried out with caution to avoid undermining communal and customary rights. The protection of lineage (hifz an-nasl) and religious principles (hifz ad-din) must also be considered to ensure that the certification process does not erode customary rights and remains consistent with Islamic law. In conclusion, the certification of Pusako Tinggi land should be conducted with caution, taking into account the alignment between state law and customary law, and prioritizing the welfare of the community in accordance with the objectives of Maqashid Syari'ah.